Refraction simulation of internal solitary waves for the fractional Benjamin-Ono equation in fluid dynamics - Duran, Serbay; Yokus, Asif; Durur, Hulya; Kaya, Dogan (World Scientific Publ Co Pte Ltd, 2021)
In this study, the modified (1/G')-expansion method and modified sub-equation method have been successfully applied to the fractional Benjamin-Ono equation that models the internal solitary wave event in the ocean or atmosphere. With both analytical methods, dark soliton, singular soliton, mixed dark-singular soliton, trigonometric, rational, hyperbolic, complex hyperbolic, complex type traveling wave solutions have been produced. In these applications, we consider the conformable operator to which the chain rule is applied. Special values were given to the constants in the solution while drawing graphs representing the stationary wave. By making changes of these constants at certain intervals, the refraction dynamics and physical interpretations of the obtained internal solitary waves were included. These physical comments were supported by simulation with 3D, 2D and contour graphics. These two analytical methods used to obtain analytical solutions of the fractional Benjamin-Ono equation have been analyzed in detail by comparing their respective states. By using symbolic calculation, these methods have been shown to be the powerful and reliable mathematical tools for the solution of fractional nonlinear partial differential equations.
Keywords: Modified (1/G ')-expansion method; modified sub-equation method; exact solution; internal solitary wave; conformable derivative